KESIAPAN PEMERINTAH KABUPATEN/KOTA PROVINSI KALIMANTAN TIMUR MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Thomas Robert Hutauruk; Salasiah Salasiah; Jamli Jamli (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2016)
AbstractAlong with the implementation AEC 2015, required the officer is capable of controlling the situation. The research location chosen were the cities of Samarinda, Balikpapan, Bontang, and Berau. This research sampling method using purposive sampling and using qualitative descriptive analysis from Spradley approach. The results showed that the technical personnel in the area have the ability of public services are quite good, because it has been programmed to follow the training in stages, but there are no areas that have caused doubt MEA-related regulations in the area of personnel in the act.Key Words: AFTA, Government Agencies, MEA